Geoarcheological simulation of western Kentucky Middle and Late Archaic settlement patterns. - Leach, Elizabeth Katrin (1991)
Geoarcheological studies have traditionally emphasized the regional environmental or the site-specific contexts of archeological entities. These traditional approaches are compared with those of paleoethnobotany and zooarcheology to suggest additional applications of geoarcheology to anthropological problems in an archeological context. The reorientation of geoarcheology that results emphasizes cultural aspects of the relation between persons and the geologic environment. From this reoriented perspective on geoarcheology the changes in settlement patterns of western Kentucky's Middle and Late Archaic are addressed. These changes have been noted as a decrease in site size and a shift from depositional to non-depositional environments from the Middle to the Late Archaic. A simulated archeological record is created to examine the interplay among geologic, botanical, and anthropological factors controlling these settlement patterns. The simulated record results from three programs that model its nutritional basis, the settlement system that generates sites, and external factors that destroy or preserve sites occupied. The simulation uses qualitative rule-based modelling in conjunction with quantitative methods to produce the record. The simulation results are compared to the results of archeological survey by the Lower Cumberland Archeological Project. The comparison suggests that the apparent differences in settlement patterns between the Middle and Late Archaic can result from responses by a single settlement system to changing environmental conditions from Middle to Late Holocene time. Reordering of arboreal species across the landscape and changes in the local water table are suggested as the environmental factors that affected settlement patterning. A later date for first heavy frost during the Middle Holocene is suggested as the major environmental factor affecting length of occupation at particular settlements. PhD Archaeology Earth Sciences Geology Native American studies Paleoecology Social ...